Factors Influencing Compliance With The Use of Personal Protective Equipment (PPE) Among Staff In The National Clinical Pathology and Microbiology Laboratory of Timor-Leste - Edy Barreto Fátima, Joana Melanya Das Dores; Roga, Anderias Umbu; M. Ratu, Jacob; Bale, Jefri S.; Tamelan, Paul G. (Journal of Neonatal Surgery, 2025)
The use of Personal Protective Equipment (PPE) in microbiology and clinical pathology laboratories is essential to safeguard laboratory staff from occupational hazards such as infectious agents, chemicals, and toxic substances. Despite its importance, non-compliance remains a persistent issue, particularly in the National Clinical Pathology and Microbiology Laboratory of Timor-Leste. This study aims to analyze the factors influencing compliance with PPE usage among laboratory staff in Timor-Leste. This research employs a cross-sectional design with a mixed-methods approach, integrating the collection, analysis, and "mixing" of quantitative and qualitative data at various stages within a single study. The study population consists of a quantitative group, which includes all workers in the Clinical Pathology and Microbiology Laboratory, and a qualitative group comprising the Laboratory Director, Department Heads, lab technicians, administrative staff, and cleaning personnel. The quantitative sample size consists of 30 respondents, selected through purposive sampling. Data collection methods include questionnaires and in-depth interviews with qualitative participants. Pearson correlation analysis revealed no significant relationship between knowledge (p-value = 0.118, PR = 1.45; 95% CI = 0.85–2.50; r = 0.292), training (p-value = 0.796, PR = 0.95; 95% CI = 0.50–1.80; r = 0.049), and PPE availability (p-value = 0.406, PR = 0.80; 95% CI = 0.40–1.60; r = -0.157) with compliance to PPE usage. These findings highlight the need for enhanced supervision and enforcement of regulations, the provision of adequate and high-quality PPE, and continuous occupational health and safety training